The Relationship between the Level of Knowledge and Attitude of Mother Toward the Incidence of Stunting in Liwuto Village, Kokalukuna Subdistrict, Baubau City - Rina Anwar; Juwitriani Alwi; Waode Suiyarti (Sean Institute, 2023)
Stunting is a condition of growth failure that occurs in children under five due to chronic malnutrition so that children look short at their age. There are many factors that cause stunting, including maternal knowledge and attitudes. The purpose of this study was to determine the relationship between maternal knowledge and attitudes with the incidence of stunting in toddlers. The method used in this study was a cross sectional study with the research subjects were mothers who had babies 1-5 years old in Liwuto Village, Kokalukuna Subdistrict, Baubau City. Data analysis used chi-square for knowledge variables and Fisher's Exact for attitude variables. The results of this study showed that the incidence of stunting among toddlers was 64.3%. Based on bivariate analysis of the relationship between maternal knowledge and the incidence of stunting, the value of p < 0.05 (p = 0.024) and bivariate analysis of the relationship between maternal attitudes and the incidence of stunting, the value of p < 0.05 (p = 0.019). The results of this study indicate that there is a significant relationship between the level of knowledge and attitudes of mothers with the incidence of stunting in toddlers in Liwuto Village, Kokalukuna Subdistrict, Baubau City.